Peculiarities of toxicodynamics and hazard assessment of pymetrozine,a new insecticide - Korshun M.M.; Ruda T.V.; Blagaia А.V.; Antonenko A.M. (Medičnì Perspektivi)
It is well known that despite an actual efficiency pesticides can have a negative impact on humans, animals and the environment. So, new pesticides must be regulated at the stage of their registration in order to prevent such a harmful effect of chemical crop protection agents (CCPA). In this context, the aim of our study was to assess the danger by using toxicological criteria and substantiate acceptable daily intake (ADI) of pymetrozine for humans. It was performed the expert-analytical study of the primary and secondary sources of information during study of its toxicity on laboratory animals. It was established that pymetrozine is related to 2 class of hazard (limiting indication is inhalation toxicity). In chronic study the lowest NOAEL on rats was set at 10 ppm (0,337 mg/kg) for systemic toxicity, which made it possible to substantiate ADI of pymetrozine for a human at 0,003 mg/kg. The definition of this criterion will allow to set a series of hygienic standards to be followed, without any harmful effect on a human.